Personal learning environment framework for a self-help Maqam-based search system - Othman, Roslina; Noordin, Mohamad Fauzan; Tengku Sembok, Tengku Mohd; Zeki, Akram M.; Mior Ibrahim, Emma Nuraihan; Hamid Kazi, Sadia; Abdul Karim, Siti Raudah (IEEE, 2014)
In this era of technology and ICT, learners and tutors are moving towards self-learning and self-set goals. Personal Learning Environments (PLE) are systems that enable learners to manage their own learning process for attaining a specific goal. PLEs interconnect and integrate both formal and informal learning with self-regulated learning in tertiary education. Most of the PLEs are adopted at universities for learners to collaborate and share their ideas and content using different tools, communities and services. In this paper, we have created the architecture for a Personal Learning Environment specifically for the Self-help Maqam- based Search System built upon the seven maqams outlined in Al-Ghazali’s Minhajul Abidin. This self-help system assesses a person’s current state (maqam) of spirituality with an opportunity to learn ways of improving one’s spiritual state as defined in Minhajul Abidin. Thus, we developed a pedagogical framework by combining self-regulated learning and metacognitive knowledge first, so that the framework could be used to map the Personal Learning Environment (PLE) into the Self-help Maqam-based Search System mentioned above.